Conceptualization of employer brand dimensions in Malaysia luxury hotels - Mohamad, Siti Fatimah; Md Sidin, Samsinar; Zawawi, Dahlia; Ho, Jo Ann; Boo, Huey Chern (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Employer branding has been suggested as an approach to combat employee high turnover, unattractive organizational image and low-quality workforce issues. It concerns on how an organization portrays its image to potential employees, current employees, and other related stakeholders. Organizational attraction can be achieved by identifying specific employer brand dimensions. However, the conceptualization of employer brand is still in an infant stage, particularly from the perspective of current employees. Most of the employer brand studies were conducted within the context of potential employees, where their perspectives might be misleading as they have no work experience. The perspectives from potential employees could not be applied to the context of current employees. Thus, the aim of this study is to conceptualize the employer brand by identifying its dimensions from the perspectives of current employees in Malaysia luxury hotels. An employer brand survey instrument consisted of twenty-five items was adopted from a previous study. 1035 forms were distributed to the employees in Malaysia luxury hotels, and this study managed to analyze 436 of usable responses. Exploratory factor analysis and confirmatory factor analysis were conducted to discover and to confirm the number of employer brand dimensions from the context of Malaysia luxury hotels. Three dimensions of employer brand were developed from this study: organization, individual and growth. Each of the employer brand dimension encompasses components that give direction in attracting and retaining employees. It is anticipated that this study will shed some light on the issue of employer brand, particularly within the context of the Malaysia hospitality industry. In addition, hotel managers will be able to strategize the employer branding in their organization according to the dimensions suggested by this study.